Polymer blend membranes for CO2 separation from natural gas - Mukhtar, H. (Institute of Physics Publishing, 2016)
Polymeric membranes are dominantly used in industrial gas separation membrane processes. Enhancement in membranes permeability and/or selectivity is a key challenge faced by membrane researchers. The current work represents the effect of poyetherimide blending on separation performance of polysulfone membranes. Polysulfone/poyetherimide (PSF/PEI) blend flat sheet dense membranes were synthesized and tested for permeation analysis of CO2 and CH4 gases at 6, 8 and 10 bar pressure and 25oC temperature. Morphology and thermal properties of membranes were characterized by field emission scanning electron microscope (FESEM) and thermo gravimetric analysis (TGA) respectively. Blend membranes were dense and homogeneous as deduced from FESEM analysis. Thermal stability of synthesized blend membranes was maintained by blending with PEI as characterized by TGA results. Decrease in permeability of both gases was observed by the addition of PEI due to rigidity of PEI chains. Additionally, selectivity of synthesized blend membranes was enhanced by blending PEI and blend membranes show improved selectivity over pure PSF membrane. This new material has the capability to be used as gas separation membrane material. Â© Published under licence by IOP Publishing Ltd.